Phosphatidylethanolamine-binding protein 4 deficiency exacerbates carbon tetrachloride-induced liver fibrosis by regulating the NF-κB signaling pathway - Luo, Qianqian; Ling, Yuanyi; Li, Yufei; Qu, Xiaoqin; Shi, Qiaoqing; Zheng, Shuangyan; Li, Yanhong; Huang, Yonghong; Zhou, Xiaoyan (Frontiers in Pharmacology, 2022)
Liver fibrosis is a pathological process which can progress to hepatocirrhosis, even hepatocellular carcinoma. Phosphatidylethanolamine-binding protein 4 (PEBP4) is a secreted protein involved in regulating many molecular pathways, whereas its roles in diseases including hepatic fibrosis remain undefined. The nuclear factor-κappa B (NF-κB) signaling pathway has been found to be involved in the development of liver fibrosis. In this study, we generated a hepatocyte-conditional knockout (CKO) mouse model of PEBP4, and explored the potential functions of PEBP4 on liver fibrosis and the NF-κB signaling pathway in a mouse model of carbon tetrachloride (CCl4)-induced liver fibrosis. We demonstrated that PEBP4 CKO aggravated CCl4-triggered liver fibrosis, as evidenced by altered histopathology, an increase in the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and hydroxyproline (HYP), and more collagen deposition, as well as by enhanced expression of fibrotic markers including α-smooth muscle actin (α-SMA), collagen I and collagen III. Mechanistically, PEBP4 deficiency activated the NF-κB signaling pathway, as indicated by increased phosphorylation of NF-κB p65 and inhibitor protein κB inhibitor-α (IκB-α), and nuclear NF-κB p65 expression in the fibrotic liver. Notably, the NF-κB inhibitor pyrrolidine dithiocarbamate (PDTC) partially blocked the activation of the NF-κB pathway, and reversed the pro-fibrotic effect of PEBP4 deletion in CCl4-treated mice. Together, these results suggest that PEBP4 deficiency results in aggravation of liver fibrosis and activation of the NF-κB signaling pathway, supporting a novel concept that PEBP4 is a crucial player in hepatic fibrosis, but also might be a negative regulator of the NF-κB signaling in liver fibrosis.